E-Absensi Berbasis Web Pada Satker BID TIK POLDA Jambi - Manurung, Hery; Siahaan, Kondar (LPPM Universitas Dinamika Bangsa, 2022)
The development of information technology must be followed by all work units, including in this case the Jambi Regional Police, where the Jambi Regional Police have several work units (Satker) which include the Information and Communication Technology Sector or in short the BID TIK. BID TIK Regional Police Legal Area Jambi Province or abbreviated POLDA Jambi Is the implementing element of the special staff of the Regional Police under the Jambi Regional Police Chief or abbreviated as Kapolda. Serves as a builder and organizer of an information system which includes data collection and collection, analysis and evaluation as well as information presentation including multimedia services, as a criminal information center, including services, one of which is percentage. In accordance with this need, a prototype system design was made that can assist personnel attendance and attendance management in the Jambi Police BID TIK work unit